Study and characterization of indium oxynitride photoconductors - M. Sparvoli; R. D. Mansano; J. F. D. Chubaci (Materials Research, 2013)
Multifunctional materials are a new class of thin films and coatings. These materials show interesting characteristics for application in many scientific areas, in special electronic and photonic technologies. These characteristics include sensitivity for thermal, light, mechanical, chemical and other influences, high resistivity, high electrical isolation and transparence in visible range. Recently it was obtained a new oxide type that combines oxygen, nitrogen and indium: the indium oxynitride. In this work, we study the deposition of indium oxynitride by reactive sputtering for application in photoconductor sensors. The deposition processes were performed in a home build magnetron sputtering system, using a four-inch pure In target, nitrogen and oxygen as process gases. The pressure was kept constant at 10 mtorr and the RF power (13.56 MHz) was constant at 250 W. The photoconductors were made with these thin films. The photoelectric detectors were analyzed by IxV (current versus voltage) analyses. The IxV analysis presented a low leakage current (10-8 A). The photoelectric effect was observed from the difference between the case with emitted light and dark currents. It increased around 140 times, under illumination of a halogen lamp. The Hall Effect measurements indicated that the films were n-type semiconductors. The increase in the oxygen concentration added in the plasma, promoted the change in the character of these thin films from conductor to semiconductor material.